Plasmid-Mediated Spread of Carbapenem Resistance in Enterobacterales: A Three-Year Genome-Based Survey - Yancheng Yao; Can Imirzalioglu; Linda Falgenhauer; Jane Falgenhauer; Petra Heinmüller; Eugen Domann; Trinad Chakraborty (2024)
The worldwide emergence and dissemination of carbapenem-resistant Gram-negative bacteria (CRGNB) is a challenging problem of antimicrobial resistance today. Outbreaks with CRGNB have severe consequences for both the affected healthcare settings as well as the patients with infection. Thus, bloodstream infections caused by metallo-ß-lactamase-producing